Differences in thyroid function between small for gestational age and those with appropriate weight for gestational age. Is thyroid function normal in small for gestational age newborns? - Iker Fernández González (Elsevier, 2021)
Introduction: Several studies conclude that small for gestational age (SGA) children have a higher number of comorbidities, as well as a different hormonal profile compared to those with appropriate weight for gestational age (AGA). Thyroid hormones play an important role in growth and neurocognitive development. Thyroid function in SGA children is still not completely known. Objectives: To compare the thyroid function of SGA children during the first 2 years of life with that in publications on thyroid function in other groups of infants, such as AGA and premature children, using the same methodology. Methods: A cohort of 38 SGA children was obtained, in which the thyrotropin (TSH) values in blood were measured at different points in the development of the SGA child. The results were compared with a population of AGA children from Zaragoza and a population of premature children from Barcelona by comparing the means using a 2-tailed test. Results: A statistically significant difference (P < 0.05) was observed between the SGA children in our study and the AGA children older than 6 months, but not between the SGA children of the study and the population of premature infants. Conclusions: SGA children have higher TSH values compared to AGA children older than 6 months. Therefore, it seems reasonable to establish a screening and a follow-up protocol in those SGA with high risk to develop thyroid dysfunction. Resumen: Introducción: Múltiples estudios concluyen que los niños pequeños para la edad gestacional (PEG) tienen un número mayor de comorbilidades, así como un perfil hormonal diferente respecto a los niños con un peso adecuado para la edad gestacional (PAEG). Las hormonas tiroideas juegan un papel importante en el crecimiento y en el desarrollo neurocognitivo. La función tiroidea en los niños PEG es, hoy en día, incierta. Objetivos: El objetivo de este estudio es comparar la función tiroidea de los niños PEG durante los 2 primeros años de vida con publicaciones sobre función tiroidea en otros grupos de lactantes (PAEG y prematuros) que utilicen la misma metodología. Métodos: Se obtuvo una cohorte de 38 niños PEG, en los cuales se midieron los valores de TSH en sangre en distintos momentos del desarrollo del niño PEG. Los resultados se compararon con una población de niños PAEG de Zaragoza y una población de niños prematuros de Barcelona mediante pruebas de comparación de medias de contraste bilateral. Resultados: Se ha observado una diferencia estadísticamente significativa (p < 0,05) entre los niños PEG de nuestro estudio y los niños PAEG mayores de 6 meses, no así entre los PEG del estudio y la población de prematuros. Conclusiones: Los niños PEG tienen valores de TSH superiores respecto a los niños PAEG mayores de 6 meses. Por lo tanto, parece razonable establecer un cribado y un protocolo de seguimiento en los PEG de mayor riesgo.